2011
DOI: 10.1007/s10230-011-0138-4
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Quantify Na-Fluorescein (Uranine) in Acid Mine Waters

Abstract: Sodium fluorescein (uranine) is one of the most popular fluorescent dyes for tracer experiments due to its chemical properties, low detection limits and low costs. As a limiting factor, it is generally assumed that Na-fluorescein cannot be properly detected under acid conditions because of weak fluorescence intensities at the standard excitation wavelength (490 nm). This laboratory study introduces a method to quantify Na-fluorescein in low pH waters without having to raise pH to alkaline conditions, which spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…However, results from the laboratory investigation showed that uranine fluorescence recovered when acidic conditions were re-neutralized to the pH values observed in samples collected at the St. Louis Tunnel portal (pH 7.34), which were likely maintained by reversible ion exchange reactions [18,23]. The study results therefore support previous recommendations from Naurath et al [23] that uranine can be successfully used in mine tracer studies when samples analyzed for tracer recovery are alkaline.…”
Section: Shaft To St Louis Tunnel Portalsupporting
confidence: 80%
See 4 more Smart Citations
“…However, results from the laboratory investigation showed that uranine fluorescence recovered when acidic conditions were re-neutralized to the pH values observed in samples collected at the St. Louis Tunnel portal (pH 7.34), which were likely maintained by reversible ion exchange reactions [18,23]. The study results therefore support previous recommendations from Naurath et al [23] that uranine can be successfully used in mine tracer studies when samples analyzed for tracer recovery are alkaline.…”
Section: Shaft To St Louis Tunnel Portalsupporting
confidence: 80%
“…The RWT dye was run with 550/580 nm excitation/emission and the uranine was run with 492/512 nm excitation/emission. The excitation and emission values for both dyes were within the expected variability [19] of values previously reported for fluorescence analysis of these dyes [8,18,23]. For RWT, a 5-point calibration curve was developed using standards between 1 and 400 ppb concentration.…”
Section: Tracer Sampling and Analysismentioning
confidence: 99%
See 3 more Smart Citations